All eggs in one basket: A critical reflection on Malawi's developpment strategies - Droppelmann, Klaus; Makuwira, Jonathan; Kumwenda, Ian (Pennsylvania State University Press, 2012)
This paper analyzes structural transformation in Malawi, a poor landlocked country with very high dependence on agriculture. For many decades, Malawi's development strategies were dominated by the development of the estate sector. In more recent years the focus has rightly shifted to facilitate productivity growth for the dominant smallholder population. Yet despite positive developments on that front, the economy remains precariously dependent on the predominantly rainfed production of just two major crops (maize and tobacco). Urban areas, including small rural towns, remain small and underdeveloped, and transport costs are extremely high. This suggests an urgent need for policymakers to plan for greater economic diversification, including the development of higher value agricultural commodities and agro-processing.